(untitled) (Menara Perkebunan, 2016)
Summary Genetic engineering of robusta coffee for resistance to pathogenic fungi is considered to be one of the potential approaches to overcome the problem at robusta coffee plantation caused by pathogenic fungi. This research was aimed to introduce chitinase (CHI) gene into embryogenic calli of robusta coffee and regenerate the plantlets. Embryogenic calli were co-cultivated with Agrobacterium tumefaciens LBA4404 harboring pCAMBIA1301 which contains chitinase gene under 35S promoter. In this research four concentrations (0, 50, 100 and 150 mg/L) of acetosyringone (AC) were used in the co-cultivation medium. Selection for transformed calli was conducted by gradually increasing the concentration of hygromicin from 5 to 25 mg/L. Somatic embryo (SE) was induced from callus on the medium containing a combination of BAP 5 mg/L and IAA (0, 0.25 or 0.50 mg/L). Integration CHI in plant genome was examined by GUS assay and PCR. The result revealed that among the four AC concentrations tested, 100 mg/L gave the highest percentage of calli growing on the selection medium (42.5%). BAP concentration of 5 mg/L alone was the most effective for inducing of SE from transformed calli with the highest percentage of 43.1% and average number SE of 8.8 ± 3. The strongest GUS expression on the calli at 3 days after transformation and the calli grown on selection medium containing 150 mg/L AC, which were 56.5% and 40% respectivelly. PCR analysis showed that 7 out of 12 plantlets tested, contained CHI gene. From this research 28 transgenic plantlets of robusta coffee were obtained Ringkasan Rekayasa genetika untuk merakit tanaman kopi robusta tahan jamur pathogen dipandang merupakan salah satu pendekatan alternatif yang potensial untuk mengatasi masalah pada perkebunan kopi robusta akibat serangan jamur patogen. Penelitian ini bertujuan untuk meng- introduksikan gen kitinase (CHI) ke dalam kalus embriogenik kopi robusta dan regenerasinya menjadi planlet, sebagai upaya untuk merakit tanaman kopi robusta tahan serangan jamur. Kalus embriogenik diko-kultivasi dengan Agrobacterium tumefaciens LBA4404 pembawa pCAMBIA1301 yang mengandung gen kitinase di bawah kontrol promotor 35S. Pada percobaan ini, empat konsentrasi asetosiringon (AS) (0, 50, 100 dan 150 mg/L) digunakan dalam medium ko- kultivasi. Seleksi kalus hasil transformasi dilakukan dengan peningkatan konsentrasi higro- misin secara bertahap dari 5 mg/L sampai 25 mg/L. ES diinduksi dari kalus pada medium yang mengandung BAP 5 mg/L dan IAA (0; 0,25 dan 0,50 mg/L). Integrasi gen CHI ke dalam genom tanaman dianalisis melalui uji GUS dan PCR. Hasil penelitian menunjukkan bahwa dari keempat konsentrasi AS yang diuji, AS 100 mg/L ternyata menghasilkan persentase tertinggi kalus yang tumbuh pada medium seleksi (42,5%). Konsentrasi BAP 5 mg/L tanpa penambahan IAA efektif menginduksi ES dari kalus hasil transformasi dengan persentase tertinggi 43,1% dan rata-rata jumlah ES 8,8±3. Ekspresi GUS tertinggi dideteksi pada kalus tiga hari setelah transformasi dan kalus yang tumbuh di medium seleksi yang mengandung AS 150 mg/L, masing-masing 56,5% dan 40,0 %. Analisis PCR menunjukkan bahwa 7 planlet dari 12 planlet yang diuji, membawa gen CHI. Dari penelitian ini dihasilkan 28 planlet kopi robusta transgenik.